Social entrepreneurship and intersectionality: Mitigating extreme exclusion - Qureshi, Israr; Bhatt, Babita; Sutter, Christopher; Shukla, Dhirendra Mani (Journal of Business Venturing, 2023)
As social enterprises seek to share knowledge, they must navigate social hierarchy. In this study, we examine social enterprises' efforts to share knowledge in rural areas and how they seek to mitigate some of the consequences of women's marginalization during this process. We use a two-step, multi-method approach. We begin with a quantitative study that explores outcomes for women, and how caste and patriarchy influence their ability to adopt new practices introduced by social enterprises. We then draw on data from a seven-year qualitative case study to unpack our quantitative findings and explore the actual mechanisms through which intersectionality shapes the social enterprises' efforts. Our qualitative efforts also uncover how social enterprises' practices, as well as women's activities, can mitigate some of the negative consequences of marginalization, even while the social setting is largely unchanged. We seek to contribute to theory by exploring how social enterprises can potentially mitigate some of the negative consequences of exclusion due to intersectionality.